Racial and Ethnic Disparities in Neurological Care in the United States - Perez, Michael A.; Reyes-Esteves, Sahily; Mendizabal, Adys (Seminars in Neurology, 2024)
The burden of neurological disease is increasing globally. In the United States, this burden is disproportionally greater for Black and Latino communities who have limited access to neurological care. Health services researchers have attempted to identify racial and ethnic disparities in neurological care and possible solutions. This article reviews the most current literature on racial and ethnic disparities in commonly encountered neurological conditions, including Stroke, Alzheimer's Disease, Multiple Sclerosis, Epilepsy, Parkinson's Disease, and Migraine. Disparities exist in disease incidence, diagnosis, access to care, treatment, outcomes, and representation in epidemiologic studies and clinical trials. Many of the disparities observed in neurological care in the United States are a consequence of longstanding racist and discriminatory policies and legislation that increase risk factors for the development of neurological disease or lead to disparities in accessing quality neurological care. Therefore, additional efforts on the legislative, community health, and healthcare system levels are necessary to prevent the onset of neurological disease and achieve equity in neurological care.
Keywords: racial disparities; ethnic disparities; neurological care